2018
DOI: 10.4066/biomedicalresearch.29-18-914
|View full text |Cite
|
Sign up to set email alerts
|

Comparative biochemical and histopathological studies on the efficacy of metformin and Nigella sativa oil against thioacetamide-induced acute hepatorenal damage in rats

Abstract: Background: Metformin is the first-line oral anti-diabetic drug and Nigella sativa (NS) have been used as traditional medicine to cure/prevent a wide range of diseases in different part of the world, particularly in Saudi Arabia. Objective: To carry out the comparative biochemical and histopathological studies on the efficacy of metformin, Nigella sativa oil (NSO) against thioacetamide (TAA)-induced acute hepatorenal damage in rats. Materials and methods: Forty-eight male Albino Wistar rats were randomly divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Since Met is positively charged, it enters into the mitochondria of hepatocytes and inhibits ATP production, which in turn, results in the acute inhibition of gluconeogenesis. Also, it was previously reported that Met suppresses liver inflammation by inhibiting interleukin-6-stimulated inflammatory response via activation of AMP-activated protein kinase (AMPK) (44). Moreover, Met may promote the stabilization of phospholipid in the cell membrane thereby preserving cell integrity, and ultimately prevents the cellular escape of cytoplasmic components and enzymes from the hepatocytes into the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…Since Met is positively charged, it enters into the mitochondria of hepatocytes and inhibits ATP production, which in turn, results in the acute inhibition of gluconeogenesis. Also, it was previously reported that Met suppresses liver inflammation by inhibiting interleukin-6-stimulated inflammatory response via activation of AMP-activated protein kinase (AMPK) (44). Moreover, Met may promote the stabilization of phospholipid in the cell membrane thereby preserving cell integrity, and ultimately prevents the cellular escape of cytoplasmic components and enzymes from the hepatocytes into the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained serum was then held back at lower temperature (2-3°C) for further measurement of different biochemical study. Serum insulin and glucose levels were determined by enzymatic methods with the help of an automated analyzer (Dimension Vista® system, Siemens, Germany) using standard biochemical kits [19]. 2.8.…”
Section: Estimation Of Biochemical Parametersmentioning
confidence: 99%
“…It has been reported in many studies that cisplatin, when administered, can be retained in the body for as long as 20 years. It has a protective effect on different kinds of tissues like the heart, kidney (Ahmad & Alkreathy, 2018;Hassan, Akhtar, Ahmed, Ahmad, & Najmi, 2017;Nagi, Al-Shabanah, Hafez, & Sayed-Ahmed, 2011), skin, and liver (Jaswal, Sinha, Bhadauria, Shrivastava, & Shukla, 2013). Endogenous antioxidants in therapeutic herbs may assume a critical part as a defense against oxidative damage and ensure the biological functions of cells (Gaikwad, Dagle, Choughule, Joshi, & Kadam, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thymoquinone (TQ), a flavonoid derived from Nigella sativa seeds, generally known as black cumin, is diversely used in traditional medicinal systems to treat various ailments (Ahmad et al, , 2014. It has a protective effect on different kinds of tissues like the heart, kidney (Ahmad & Alkreathy, 2018;Hassan, Akhtar, Ahmed, Ahmad, & Najmi, 2017;Nagi, Al-Shabanah, Hafez, & Sayed-Ahmed, 2011), skin, and liver (Jaswal, Sinha, Bhadauria, Shrivastava, & Shukla, 2013). Recent findings have concluded that TQ has an ameliorative effect against oxidative stress and inflammatory responses (Mahmoud, Ahmed, & Galaly, 2014).…”
Section: Introductionmentioning
confidence: 99%